Women and their rights : From totalitarianism to feminist empowerment in the context of the 20th anniversary of UN1325 on women, peace, and security between victims, leaders, and perpetrators - Zarychta-Romanowska, Kamila; Szostak, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
While analysing the heritage, input, and various implementation contexts of UNSCR 1325 on women, peace, and security, the authors investigate not only various approaches to women’s position and female empowerment in international engagement settings and cooperation models (UN, OSCE NATO, UNCDF), but also look at female empowerment in a global scope from women’s perspectives as victims, leaders, and perpetrators. By considering the need for complex engagement of international actors in stability, development, and crisis initiatives, the authors analyse NATO policy against sexual abuse and exploitation, on women’s financial inclusion, and the MenEngage initiative. While analysing the societal impact of radicalisation, they seek answers for effective reintegration and anti-radicalisation of female terrorists and foreign fighters. Authors examine the evolving gender equity and female empowerment policies of the EU in their foreign and domestic affairs, with particular interest in internal and external security standards for women’s safety
Keywords: women; peace; security; WPS; stability policing; OSCE; UN Women; NATO; UNCDF; radicalisation; foreign fighters; peacebuilding; EU; UNSCR 132; gender policies; counter radicalisation; gender based violence; international policing